Kinetics of elite unilateral below-elbow amputee running. Issue 3 (September 2016) - Mally, Franziska; Litzenberger, Stefan; Willwacher, Steffen; Braunstein, Björn; Brüggemann, Gert-Peter; Sabo, Anton
Abstract The role of the upper limbs in human locomotion and their influence on ground reaction force (GRF) have been extensively examined for walking and slow running. However, research has focused on unimpaired populations and has not evaluated high-speed running. In this study, the GRFs of an unilateral upper limb amputee athlete [missing right forearm, personal bests (PB): 400 m: 0:48.45 min, 800 m: 1:50.92 min] running at speeds of 5.4 and 8 m/s were collected using four floor-mounted force plates in a 100 m tartan track recording at 1000 Hz. The amputee athlete also performed trials with a running speed of 8 m/s wearing a weighted cuff on his impaired arm (0.5 and 1 kg, respectively). GRF data (without additional weight) were compared to those of an unimpaired athlete with similar PBs and anthropometry (age, height, weight). All data were evaluated for anterior–posterior, medial–lateral and vertical GRF as well as for stance phase (SP) duration and free moment (FM) values and a paired Student-t test ( α =5 α = 5 %) was performed on maximum and minimum values of the respective data sets comparing the left and right side of both athletes with each other, but no intersubjective comparisons were performed. The results revealed that vertical GRF showed significant differences for the impaired athlete at both running speeds comparing left and right foot, whereas the unimpaired athlete showed no significant differences in this matter at all. Medial–lateral GRF showed highly significant differences between the left and right foot of both athletes at both running speeds, whereas the results for anterior–posterior GRF and FM, however, showed ambiguous results. The trials with additional weight on the impaired limb led to significant differences for SP duration, but not for all conditions, and left–right differences did not change with additional weight. GRFs were found to differ in minimum medial–lateral GRF with no and heavy weight, maximum medial–lateral GRF within all weight conditions and maximum vertical GRF with no and heavy weight. For the FM, the overall pattern changed drastically and maximum FM showed a highly significant difference between the left and right foot, but none between the different conditions for both feet. Even though more significant asymmetries could be revealed for the impaired athlete, no general conclusion can be drawn at this point, given the limitations of the here presented study (low number of subjects available, anthropometric data of the impaired athlete could not be assessed).